2017
DOI: 10.1589/jpts.29.1085
|View full text |Cite
|
Sign up to set email alerts
|

The effects of training using EMG biofeedback on stroke patients upper extremity functions

Abstract: [Purpose] While electromyography (EMG) biofeedback has been recently used in diverse therapeutic interventions for stroke patients, research on its effects has been lacking. Most existing studies are confined to functions of the lower extremities, and research on upper extremity functional recovery using EMG biofeedback training is limited. Therefore, this study examined the effects of training using EMG biofeedback on stroke patients’ upper extremity functions. [Subjects and Methods] The subjects of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 12 publications
2
30
0
2
Order By: Relevance
“…However, in several previous studies EMG metrics have been used for biofeedback and in these studies participants are able to modulate EMG given instructions. This kind of EMG-based biofeedback has also been demonstrated to be useful for rehabilitation and prosthetic control (Dosen et al 2015;Giggins et al 2013;Kim 2017;Radhakrishnan et al 2008;Thompson and Wolpaw 2014;Woodford and Price 2007) . Lastly, although it is tempting to say that the learning we describe happens implicitly, the absence of an effect of explicit cues in this experiment does not mean that people are not engaged in different strategies (McDougle and Taylor 2019) .…”
Section: Limitationsmentioning
confidence: 99%
“…However, in several previous studies EMG metrics have been used for biofeedback and in these studies participants are able to modulate EMG given instructions. This kind of EMG-based biofeedback has also been demonstrated to be useful for rehabilitation and prosthetic control (Dosen et al 2015;Giggins et al 2013;Kim 2017;Radhakrishnan et al 2008;Thompson and Wolpaw 2014;Woodford and Price 2007) . Lastly, although it is tempting to say that the learning we describe happens implicitly, the absence of an effect of explicit cues in this experiment does not mean that people are not engaged in different strategies (McDougle and Taylor 2019) .…”
Section: Limitationsmentioning
confidence: 99%
“…Several studies have evaluated the effectiveness of biofeedback treatment on gait function in children with CP, e.g., sEMG-B of triceps surae muscle activity during gait, which may be used for improving gait symmetry in these patients (78,79). Another group of authors has demonstrated the potential benefits of sEMG-B in conjunction with exercise in maximizing hand function in hemiplegic patients (80)(81)(82) or suggested that treadmill gait retraining augmented with sEMG-B facilitates improvements in gait function in postcerebrovascular accident patients (83). These studies therefore indicate that sEMG-B is effective for post-stroke rehabilitation.…”
Section: Semg In Biofeedbackmentioning
confidence: 99%
“…In the clinical settings several types of biofeedback are used: visual, audio feedback of electromyogram, position, velocity, force values, etc [2] and can be classi ed either in physiological or biomechanical categories [3]. Potential bene ts of electromyographic (EMG) biofeedback has been demonstrated in hemiplegic patients, using the biofeedback during the exercise for hand [4], [5]. The researchers found the EMG biofeedback as a promising tool and the most widely used and reported method of biofeedback in rehabilitation [3].…”
Section: Introductionmentioning
confidence: 99%